Decomposing interaction and mediating effects of race/ethnicity and circulating blood levels of cystatin C on cognitive status in the United States health and retirement study - Higgins Tejera, César; Ware, Erin B.; Kobayashi, Lindsay C.; Fu, Mingzhou; Hicken, Margaret; Zawistowski, Matthew; Mukherjee, Bhramar; Bakulski, Kelly M. (Frontiers in Human Neuroscience, 2023)
Background and objectives: Elevated circulating cystatin C is associated with cognitive impairment in non-Hispanic Whites, but its role in racial disparities in dementia is understudied. In a nationally representative sample of older non-Hispanic White, non-Hispanic Black, and Hispanic adults in the United States, we use mediation-interaction analysis to understand how racial disparities in the cystatin C physiological pathway may contribute to racial disparities in prevalent dementia. Results: Overall, elevated cystatin C was associated with dementia (prevalence ratio [PR] = 1.4; 95%CI: 1.2, 1.8). Among non-Hispanic Black relative to non-Hispanic White participants, the relative excess risk due to interaction was 1.7 (95% CI: -0.2, 3.7), the attributable proportion was 0.2 (95%CI: 0.0, 0.5), and the synergy index was 1.4 (95% CI: 1.0, 2.0) in a fully-adjusted model. Elevated cystatin C was estimated to account for 2% (95% CI: -0%, 4%) for the racial disparity in prevalent dementia, and the interaction accounted for 9% (95% CI: -4%, 23%). Analyses for Hispanic relative to non-White participants suggested moderation by race/ethnicity, but not mediation. Discussion: Elevated cystatin C was associated with dementia prevalence. Our mediation-interaction decomposition analysis suggested that the effect of elevated cystatin C on the racial disparity might be moderated by race/ethnicity, which indicates that the racialization process affects not only the distribution of circulating cystatin C across minoritized racial groups, but also the strength of association between the biomarker and dementia prevalence. These results provide evidence that cystatin C is associated with adverse brain health and this effect is larger than expected for individuals racialized as minorities had they been racialized and treated as non-Hispanic White.